Examining Rhetorics of Play in Curricula in Five Provinces: Is Play at Risk in Canadian Kindergartens? - Stagg Peterson, Shelley; Anderson, Jim; Kendrick, Maureen; McTavish, Marianne; Budd, Kathy; Mayer, Debra; McIntyre, Laureen J; Yaman Ntelioglou, Burcu; Riehl, Dianne (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
In this article, school division and Ministry of Education–based early childhood consultants and university researchers respond to the question of whether play is at risk in kindergartens in five Canadian provinces by analyzing current and previous kindergarten curricula using Sutton-Smith’s framework of rhetorics of play. We find that play is integral to kindergarten curricula in Saskatchewan and Ontario, but only implicitly mentioned in the Alberta, British Columbia, and Manitoba curricula where support documents provide more support for play. The rhetoric of play as progress is the dominant discourse of current kindergarten curricula.